2007
DOI: 10.1074/jbc.m607213200
|View full text |Cite
|
Sign up to set email alerts
|

An Amino Acid Outside the Pore Region Influences Apamin Sensitivity in Small Conductance Ca2+-activated K+ Channels

Abstract: Small conductance calcium-activated potassium channels (SK, K Ca ) are a family of voltageindependent K + channels with a distinct physiology and pharmacology. The bee venom toxin apamin inhibits exclusively the three cloned SK channel subtypes (SK1, SK2 and SK3) with different affinity, highest for SK2, lowest for SK1 and intermediate for SK3 channels. The high selectivity of apamin made it a valuable tool to study the molecular makeup and function of native SK channels. Three amino acids located in the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 71 publications
4
37
0
2
Order By: Relevance
“…Block of SK channel current by apamin is clearly more complicated than these data suggest, as despite containing an identical outer pore sequence to the apamin-sensitive hSK1 and a serine in this position in the S3-S4 loop, rSK1 is apamin insensitive. Replacement of the S3-S4 loop of rSK1 with that of hSK1 produced a channel with a sensitivity to apamin that was similar to that of hSK1 (8). These data indicate that an additional interaction site(s) within the S3-S4 extracellular loop contributes to binding or block by apamin.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Block of SK channel current by apamin is clearly more complicated than these data suggest, as despite containing an identical outer pore sequence to the apamin-sensitive hSK1 and a serine in this position in the S3-S4 loop, rSK1 is apamin insensitive. Replacement of the S3-S4 loop of rSK1 with that of hSK1 produced a channel with a sensitivity to apamin that was similar to that of hSK1 (8). These data indicate that an additional interaction site(s) within the S3-S4 extracellular loop contributes to binding or block by apamin.…”
mentioning
confidence: 69%
“…The toxin is most potent at SK2 (IC 50 ∼ 70 pM) (5-9) and SK3 (IC 50 ∼ 0.63-6 nM) (7, 9, 10), followed by the human isoform of SK1 (IC 50 ∼ 1-8 nM) (8, 9), whereas the rat isoform of SK1 is apamin insensitive (11,12). Mutation studies have identified a number of residues within the outer pore that affect block by apamin (7,8,13). For example, an outer pore histidine residue has been shown to be critical for both binding and block by the toxin (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La pré-sence d'un résidu histidine conservé dans les trois sous-types et localisé dans la tourelle en position 490 (numérotation hSK3) s'est avérée essentielle pour le blocage des canaux par la toxine [21,49]. D'autres études complémentaires ont récemment montré que des résidus éloignés de la région du pore étaient également impliqués dans le blocage du courant par l'apamine [31,50], renforçant l'idée d'une action allostérique. Cette conclusion est confortée par le fait que les IC 50 de SK2 et SK3 sont différentes mais que leurs K d sont identiques.…”
Section: Perspectives Structurales Et Fonctionnelles Des Bloqueurs Deunclassified
“…Cet agent pré-sente une affinité pour les canaux SK (Ki ≈ 0,3 μM) environ cinq fois supérieure à celle de la NML (Ki ≈ 1,6 μM) et pratiquement équiva-lente à celle du déqualinium (Ki ≈ 0,2 μM). D'autre part, l'AG525E1 bloque de manière plus ou moins équivalente les trois sous-types de canaux SK (IC 50 • L'autre objectif important est de développer des bloqueurs présen-tant une sélectivité vis-à-vis des canaux SK assez grande pour être exploitable (elle doit être au moins 100 fois plus puissante pour l'un des sous-types). Jusqu'à présent, cette sélectivité n'a été démontrée que pour des ligands peptidiques.…”
Section: Perspectives Structurales Et Fonctionnelles Des Bloqueurs Deunclassified